Production of Gene‐Corrected Adult Beta Globin Protein in Human Erythrocytes Differentiated from Patient iPSCs After Genome Editing of the Sickle Point Mutation. (May 2015) - Huang, Xiaosong; Wang, Ying; Yan, Wei; Smith, Cory; Ye, Zhaohui; Wang, Jing; Gao, Yongxing; Mendelsohn, Laurel; Cheng, Linzhao
Abstract: Human induced pluripotent stem cells (iPSCs) and genome editing provide a precise way to generate gene‐corrected cells for disease modeling and cell therapies. Human iPSCs generated from sickle cell disease (SCD) patients have a homozygous missense point mutation in the HBB gene encoding adult β‐globin proteins, and are used as a model system to improve strategies of human gene therapy. We demonstrate that the CRISPR/Cas9 system designer nuclease is much more efficient in stimulating gene targeting of the endogenous HBB locus near the SCD point mutation in human iPSCs than zinc finger nucleases and TALENs. Using a specific guide RNA and Cas9, we readily corrected one allele of the SCD HBB gene in human iPSCs by homologous recombination with a donor DNA template containing the wild‐type HBB DNA and a selection cassette that was subsequently removed to avoid possible interference of HBB transcription and translation. We chose targeted iPSC clones that have one corrected and one disrupted SCD allele for erythroid differentiation assays, using an improved xeno‐free and feeder‐free culture condition we recently established. Erythrocytes from either the corrected or its parental (uncorrected) iPSC line were generated with similar efficiencies. Currently ∼6%–10% of these differentiated erythrocytes indeed lacked nuclei, characteristic of further matured erythrocytes called reticulocytes. We also detected the 16‐kDa β‐globin protein expressed from the corrected HBB allele in the erythrocytes differentiated from genome‐edited iPSCs. Our results represent a significant step toward the clinical applications of genome editing using patient‐derived iPSCs to generate disease‐free cells for cell and gene therapies. Stem Cells 2015;33:1470–1479